2013
DOI: 10.1016/j.burns.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hospital based Wellness and Exercise program on quality of life of children with severe burns

Abstract: Objective To examine the effect of a 12-week Wellness and Exercise (W&E) program on the quality of life of pediatric burn survivors with burns of ≥ 40% total body surface area. We hypothesized this comprehensive regimen would improve physical and psychosocial outcomes. Methods Children were recruited for participation upon their discharge from the ICU. They were not taking anabolic/cardiovascular agents. Seventeen children participated in the W&E group and 14 children in the Standard of Care (SOC) group. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
4
24
0
1
Order By: Relevance
“…A limitation of our current study is that we have not assessed psychosocial well-being or home-based exercise activities. Recent work from our institution showed that exercise positively affects psychosocial outcomes (14). Here we describe data on only exercise performance or capacity, as this was the sole focus of the current study and our major interest.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our current study is that we have not assessed psychosocial well-being or home-based exercise activities. Recent work from our institution showed that exercise positively affects psychosocial outcomes (14). Here we describe data on only exercise performance or capacity, as this was the sole focus of the current study and our major interest.…”
Section: Discussionmentioning
confidence: 99%
“…The hypermetabolic response augments proteolysis to cause loss of lean body mass, which is exacerbated by prolonged physical inactivity [5]. The resulting morbidity inhibits patients‘ return to normal societal activities and reduces quality of life [6]. One strategy that has proven effective in combating decreased lean body mass, reduced muscle strength, and reduced cardiopulmonary fitness is physical exercise [79].…”
Section: Introductionmentioning
confidence: 99%
“…In general, we know from outcome research that the majority of pediatric burn survivors achieve optimal long-term outcomes, but many continue to have long-term physical and psychological needs [1017]. We also know that participation in a structured exercise and rehabilitation program can improve physical, respiratory, and emotional functioning for pediatric burn survivors [2224]. Unfortunately, not much was previously known about the perceived long-term psychological outcome of pediatric burn survivors with inhalation injury.…”
Section: Discussionmentioning
confidence: 99%